Plato's Euthydemus - Hirsch, Darryl Bernard (My University, 1993)
This thesis is a careful examination of one small Platonic dialogue, the Euthydemus. In broad terms, it argues that the Euthydemus is concerned with what might be described as 'word games', with teaching both the need to know how to speak well and the worth of being able to do so. In more specific terms, it argues that the Euthydemus is comprised of three distinct levels, Socrates' conversation (primarily) with the brothers Euthydemus and Dionysodorus, his conversation with Crito, and Plato's conversation with the reader; levels, it is suggested, which cannot be fully understood unless Crito's role in each of them is first recognized. The first level, Socrates' conversation (primarily) with the brothers Euthydemus and Dionysodorus, is seemingly composed of three separate discussions, between Socrates and the brothers, between Socrates and Clinias, and between Socrates and Ctesippus. The first discussion is a general demonstration of knowing how to use words (or 'word games') and, further, of knowing how to use them well. The second discussion, in contradistinction to the first, centres on a coherent application of words to a specific goal; that being, to begin to demonstrate both that knowledge is the greatest good for individuals and, as well, that philosophy is nothing more than a 'perpetual ruthless questioning' . The third discussion reveals something about Ctesippus' nature. More importantly, it illustrates how words can be used to communicate with certain individuals and not others. The second level of the Buthydemus, Socrates' conversation with Crito, might accurately be described as an application of words to a specific goal writ large. The reason is that, here, Socrates tells Crito a 'story' (this being what was described above as the first level of the E:uthydemus) in order to discourage him from giving his sons a philosophic education. The third level, Plato's conversation with the reader (or Plato as distinguished from Socrates), raises the broader issue of the relation between the philosopher and the city. More precisely, it begins to reveal the effects that different methods of speaking have on an individual, on the opinions that others form as a result of his or her choice in this regard, and thus on the need for an individual to choose wisely.
Keywords: Platonic dialogue, Euthydemus, Socrates' conversation, Dionysodorus, Clinias, constradistinction, begin